Pathogenesis of Multiple Organ Failure: The Impact of Systemic Damage to Plasma Membranes - Kozlov, Andrey V.; Grillari, Johannes (Frontiers in Medicine, 2022)
Multiple organ failure (MOF) is the major cause of morbidity and mortality in intensive care patients, but the mechanisms causing this severe syndrome are still poorly understood. Inflammatory response, tissue hypoxia, immune and cellular metabolic dysregulations, endothelial and microvascular dysfunction are the main features of MOF, but the exact mechanisms leading to MOF are still unclear. Recent progress in the membrane research suggests that cellular plasma membranes play an important role in the key functions of diverse organ. Exploration of mechanisms contributing to plasma membrane damage and repair suggest that these processes can be the missing link in the development of MOF. Elevated levels of extracellular phospholipases, reactive oxygen and nitrogen species, pore forming proteins, and dysregulation of osmotic homeostasis occurring upon systemic inflammatory response are the major extracellular inducers of plasma membrane damage, which may simultaneously operate in different organs causing their profound dysfunction. Hypoxia also activate similar processes, but they predominantly occur within the cells targeting intracellular membrane compartments and ultimately causing cell death. To combat the plasma membrane damage cells have developed several repair mechanisms, such as exocytosis, shedding, protein-driven membrane remodeling. Analyses of knowledge on these mechanisms reveals that systemic damage to plasma membranes may be associated with potentially reversible MOF, which can be either quickly recovered if pathological stimuli are eliminated. Alternatively, it can be transformed in a non-resolving phase if repair mechanisms are not sufficient to deal with a large damage, or if the damage is extended to intracellular compartments essential for vial cellular functions.